2008
DOI: 10.1097/prs.0b013e31818820d8
|View full text |Cite
|
Sign up to set email alerts
|

Single-Splint Technique for Correction of Severe Facial Asymmetry: Correlation between Intraoperative Maxillomandibular Complex Roll and Restoration of Mouth Symmetry

Abstract: A correlation between maxillomandibular complex roll and intercommissural plane change has been demonstrated. This supports the usefulness of intraoperative change in maxillary roll to restore mouth symmetry in patients with severe facial asymmetry. It also identifies a major factor that can be modified to change mouth symmetry in the vertical plane during presurgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…However, a combination of these aspects is often present. Maxillary displacement can result in a dental midline discrepancy and/or a combination of yaw and roll of the maxilla which causes canting of both the occlusal plane and the lips (3,4). Mandibular lateral displacement is characterized by deviation of the chin from the facial midline, asymmetry of the cheeks and lower facial contour, posterior cross bite and dental and skeletal midline discrepancies (5).…”
Section: Manuscript Submissionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a combination of these aspects is often present. Maxillary displacement can result in a dental midline discrepancy and/or a combination of yaw and roll of the maxilla which causes canting of both the occlusal plane and the lips (3,4). Mandibular lateral displacement is characterized by deviation of the chin from the facial midline, asymmetry of the cheeks and lower facial contour, posterior cross bite and dental and skeletal midline discrepancies (5).…”
Section: Manuscript Submissionmentioning
confidence: 99%
“…To overcome these limits, 3D surface facial scanning has been introduced. 3D analysis of soft tissues changes after bimaxillary surgery 4 has been proposed in skeletal Class I, II and III patients (7,8,9,10). 3D analysis based on laser surface scanning has been also used for investigating facial asymmetry (11).…”
Section: Manuscript Submissionmentioning
confidence: 99%
“…9 It has been observed intraoperatively that some slight overcorrection or undercorrection might better conceal the residual soft-tissue asymmetries. 10 A set of checkpoints was gradually developed to ensure acceptable free-hand intraoperative positioning of the maxillomandibular complex to obtain aesthetic results. The traditional "intermediate splint" for sequential mandibular and maxillary repositioning was soon discarded and only the "final" occlusal splint was used to reposition the maxillomandibular complex as a unit.…”
mentioning
confidence: 99%
“…12,13 Using soft-tissue measurements based on intraoperative checkpoints, the maxillomandibular complex was repositioned free-hand as a whole. It has been shown that this technique simplify the preoperative preparation for the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…11 Because of the limitations of intermediate splint technique, the "single-splint technique" was developed for orthognathic surgery. 12,13 The traditional intermediate splint for sequential mandibular and maxillary repositioning was discarded, and only the final occlusal splint was used to reposition the maxillomandibular complex as a whole. Using soft-tissue measurements based on intraoperative checkpoints, the maxillomandibular complex was positioned free-hand to obtain the desired aesthetic results.…”
mentioning
confidence: 99%